A quadratura do círculo e a gênese do número (pi) - Vendemiatti, Aloísio Daniel (2009)
The goal of this essay is to show aspects of genesis of number π, inherent to the question of squaring the circle, which consists in constructing a square which has the same area as a given circle. This problem does not refer to a practical application of mathematics, but to the theoretic question that involves the distinction between a valid approach and thinking accuracy. The first attempt to squaring the circle dates back in the fifth century before Christ. After that, it was established that this construction should be carried through using a finite number of times, also the non-graduated ruler and the drawing compass itself. In the constructions with ruler and drawing compass we are referring to the first three postulates of Euclides Elements: 1) It´s possible to join two points by a straight line, 2) to expand a straight line until the necessary point, and 3) to draw a circumference around any point and with any radius. These postulates are the base of these constructions, sometimes called euclidean´s constructions. A real number α is constructible, if feasible building a segment of legth α with ruler and drawing compass, since a segment is taken as a unity. We show the idea of translating the geometrical problem of constructions made with ruler and drawing compass to the algebraic language and this allowed us to solve the problem of squaring the circle. We exposed that all constructible numbers are algebraic, over the rational numbers, establishing the impossibility of squaring the circle, with Lindemann´s demonstration, in 1882, of the number π transcendence. This problem has been fascinating people for more than twenty centuries. We tried to supply all mathematical tools needed for this demonstration. Demonstrations play a fundamental role in the development of this essay, which purpose is not only to contribute to the math teacher formation, but also to detail the resolution of the problem of squaring the circle